HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SMP N KECAMATAN PALEMBAYAN KABUPATEN AGAM - Hagi Eka Gusman (Universitas Negeri Padang, 2014)
This research about principal’s leadership style and teacher performance, also to see the relationship between the two variables. Population are 98 teachers and 78 samples using random sampling technique. This research instrument is a questionnaire in the form of a Likert scale, a score of variable leadership style of headmaster 0.886 and teacher performance 1.017 that means instrument is reliable. Data were analyzed using product moment correlation, for the principal’s leadership style witht teacher perfomance get r score = 0.25> = 0.220, believed r tabel standard 95%. Research has come to the conclusion the relationship between principal’s leadership style with the performance of teachers in junior high school districts palembayan districts agam. Key word: gaya kepemimpinan kepala sekolah dan kinerja